Proposta de leitura cultural e gastronômica do peixe Coró (Pomadasys corvinaeformis) e suas preparações em Camocim-Ceará - Costa, Fládia Carneiro da (2023)
Camocim, a municipality located in the state of Ceará, has fishing as one of its largest economic sources, which also contributes to feeding the natives. Coró fish is a traditional food and appears in the context of Food and Nutritional Security (SAN). The exercise of Food Sovereignty is related to the promotion of SAN, this relationship is due to the fact that it emphasizes food autonomy. This work aims to evaluate the importance of consuming Coró in culinary preparations as a proposal for reading the local gastronomy of Camocim-Ceará. To this end, the cultural importance and nutritional composition of Coró was investigated, through interviews and questionnaires to get to know the research subjects. Physicochemical and proximate composition analyzes of the fish were carried out. Culinary preparations were prepared using Coró as raw material and an analysis of their nutritional and microbiological composition was carried out. Finally, there was a sensory analysis, with a focus group on the products produced. Even though it is a fish of little economic influence, Coró has significance for Camocim fisherman. The population, in general, recognizes it as a traditional food, but does not value it as such. The most common form of consumption of Coró is fried or cooked and is consumed by different age groups and social classes. The cultural importance was more evident among the people of the sea, as the way of fishing and the way of preparation and consumption passes between generations. Fish proved to be a food with good protein content, 20%. Coró fillet had three omega 3 components, the highest being DHA. The preparations had microbiological results in accordance with legislation covering fish products. According to the sensory analysis carried out by the tasters, the Bolinho de Coró can be optimized in terms of color and texture, while the Creme de Coró was well accepted sensorially. It is suggested that a booklet be drawn up on Food Sovereignty and the importance of consuming traditional foods, with a view to introducing these subjects in schools, as well as addressing the topic in courses in the food area.